2013
DOI: 10.1111/imb.12033
|View full text |Cite
|
Sign up to set email alerts
|

An odorant receptor from the common cutworm (Spodoptera litura) exclusively tuned to the important plant volatile cis‐3‐Hexenyl acetate

Abstract: Olfaction plays an important role in insect behaviours. The odorant receptor (OR) repertoire, housed within the dendritic membrane of sensory neurons, is one of the primary determinants of odour recognition. ORs in moths could be classified into pheromone receptors (PRs) and non-pheromone receptors (non-PR ORs). Much research in the field of insect olfaction recently has been focused on PRs of the male moth, but few Lepidoptera studies have been done on the functional study of non-PR ORs. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 55 publications
2
42
1
Order By: Relevance
“…Thanks to the present results on S. littoralis ORs, receptors have now been deorphanized in 13 different clades of the lepidopteran OR phylogeny, including previous results obtained from Bombyx mori and other moths353637383940414243. To investigate the evolution of OR function in this insect order, we therefore placed these functional data in a phylogenetic framework, although it must be noted that these ORs have been deorphanized using different expression systems and different odorant panels.…”
Section: Resultsmentioning
confidence: 81%
“…Thanks to the present results on S. littoralis ORs, receptors have now been deorphanized in 13 different clades of the lepidopteran OR phylogeny, including previous results obtained from Bombyx mori and other moths353637383940414243. To investigate the evolution of OR function in this insect order, we therefore placed these functional data in a phylogenetic framework, although it must be noted that these ORs have been deorphanized using different expression systems and different odorant panels.…”
Section: Resultsmentioning
confidence: 81%
“…The selective response of AlucOR46 to plant volatiles and its female-biased expression suggest that this receptor could be involved by A. lucorum in locating host plant for feeding and oviposition [21,22,23]. …”
Section: Discussionmentioning
confidence: 99%
“…To investigate the specificity of the four selected ORs, we expressed them together with AlucOrco in Xenopus oocytes, following a strategy successfully adopted with the ORs from other insect species Sun et al, 2013;Wang et al, 2010;Zhang et al, 2013aZhang et al, , 2014. The ORs thus expressed were stimulated with an odorant collection of 71 chemicals, including green leaf volatiles (GLVs) and other terpenoids, both aliphatic and aromatic, at the concentration of 10 À4 M.…”
Section: Functional Characterization Of Alucors In the Xenopus Oocytementioning
confidence: 99%
“…Zhang et al, 2013a have identified an OR (SlituOR12) exclusively responding to (Z)-3-Hexenyl acetate from Spodoptera litura (Zhang et al, 2013a). The identity of these 4 ORs (BmorOR24, BmorOR29, SlituOR12 and AlucOR28) was only $27.8% (Supplementary material S4A).…”
Section: Functional Characterization Of Alucors In the Xenopus Oocytementioning
confidence: 99%